INTEGRASI SAINS DALAM TAFSIR AL-QUR’AN: TELAAH ATAS PENDEKATAN SAINTIFIK TAFSIR SAMUDERA AL-FATIHAH - M. Agus Muhtadi Bilhaq; Zunaidi Nur (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2025)
The scientific approach to the Quran has been a subject of debate among muslim scholars, including in Indonesia. Some view it as a form of appreciation for the scientific verses in the Quran, while others criticize this approach for relying on relative scientific theories in interpreting the Quran. In this regard, Samudera Al-Fatihah by Bey Arifin (1968) is an interesting example because it relates the interpretation of Surah Al-Fatihah to various modern scientific findings, particularly in understanding the term al-‘alamin as the macrocosm and microcosm. Therefore, this article aims to analyze Bey Arifin’s scientific approach in his interpretation of Samudera Al-Fatihah and assess the relevance of the scientific theories he uses to the latest developments in science. The method used in this study is qualitative in the form of library research, using content analysis as the data analysis method. The results of the study show that Samudera Al-Fatihah integrates various concepts of modern science, such as astronomy, biology, and physics, in explaining the term al-‘alamin. This interpretation not only demonstrates the synergy between revelation and reason but also makes an early contribution to introducing a scientific approach within the Indonesian tradition of Quranic exegesis. Although the scientific theories employed are not immune to criticism regarding their relevance to the times, the Samudera Al-Fatihah remains one of the interpretations that pioneered the use of a new approach in understanding Quranic verses through science.